Interreligious Engagement Between Indigenous Religion and Christianity Within the Huaulu Community in Maluku - Paais, Vikry Reinaldo (Al-Albab, 2025)
The arrival of Western Christianity in the archipelago, alongside European expansion, solidified Christian dominance and asserted superiority over indigenous religious practices. European supremacy did not merely bolster this dominance but also fueled theological narratives that portrayed indigenous religions as “dark” and “heretical,” necessitating their conversion to Christianity. This framework shaped interfaith discourse, marginalizing indigenous religions and excluding them from meaningful engagement. This article aims to analyze the socio-religious engagement between the adherents of Memaham (an indigenous religion) and Christians in the context of interreligious relations. This research was conducted within the Huaulu indigenous community, North Seram District, Central Maluku Regency, Maluku Province. This study employs a participatory qualitative research methodology, using interviews and observations as data generation methods. The findings reveal that Memaham, as the indigenous religion of the Huaulu, experienced a complex and dynamic engagement with Christianity, such as harmonious collaboration, ongoing negotiation, and even direct confrontation. Those findings provide an empirical contribution to interreligious relations within a postcolonial context, by aiming to avoid the romanticization often oriented towards harmonious relationships.